PENGARUH TINDAKAN SPINAL ANESTESI TERHADAP KADAR GULA DARAH PADA PASIEN OPERASI SECTIO CAESAREA DI RUMAH SAKIT PERTAMEDIKA UMMI ROSNATI BANDA ACEH - Muhammad Syakir Marzuki; Fauziah Hayati (Jurnal Sains Riset, 2021)
The process of surgery and anesthesia will actually cause a stress response. Changes in body response that occur due to anesthesia can cause activation of the sympatic nervous system, hormonal and metabolic changes thereby increasing the secretion of neuroendocrine hormones. An increase in gluconeogenesis due to increased secretion of cortisol, glucagon, and catecholamines cause an increase in blood sugar levels. The purpose of this research was to determine effect of sinal anesthesia on blood sugar levels before and after section caesarea. This study is an analytic descriptive observational with cross sectional method by using 30 samples with causacutive sampling. The result of research based on the wilcoxon test obtained p-value 0,000 0,05. It shows that there is a strong relation between spinal anesthesia with blood sugar levels in section caesarean patients at Pertamedika Ummi Rosnati Hospital, Banda Aceh. The recommendation of this research are expected to be useful for future research on anesthesia and section caesarea.Keywords: spinal anesthesia, section caesarean, blood sugar